Correlates Of Job Motivating Factors Among Male Health Workers in Rural Karnataka - Gupta, Manoj Kumar; Reddy, K Sreenath; Veena R; Prabha, Chandra; Chandana M (National Journal of Community Medicine, 2013)
Introduction: This study was planned to assess the correlate of job motivating and de-motivating factors with the actual situation among male health workers (MHWs) in rural Karnataka. Methodology: A cross sectional study design was adopted. From Karnataka state, six districts were selected for the study by adopting appropriate sampling methodology. Out of the total sub-centers in those selected districts, 49 were selected based on confirmation of position of Male Health Workers at the sub centers. Those MHWs were interviewed by using a structured interview schedule. Data was analyzed using Microsoft excel 2007 and SPSS v.16 software. Results: Stable job and income was addressed as job motivational factor in 87.8% of MHWs. Convenient location with proper connectivity of SC was motivating factor for nearly 70% Of MHWs. Majority (95.9%) of MHWs were considering sense of achievement and recognition as job motivation factor irrespective of their working years. Conclusion: A moderate discrepancy was found between job motivating and de-motivating factors with the actual situation. Hence, there is huge scope and need to explore those factors with some multi centric studies.